Analisis Proses Berpikir Matematis Siswa dalam Menyelesaikan Soal Pemecahan Masalah Matematika - Khairunnisa, Khairunnisa; Herman, Tatang; Juandi, Dadang; Siagian, Qania Agustika (Edumatica : Jurnal Pendidikan Matematika, 2022)
Mathematics learning activities in schools tend to emphasize students to be able to solve problems with existing formulas. Likewise, teachers who pay less attention to and practice various problem-solving strategies. Thus, students are less able to express their thinking processes. This study aims to determine the students' mathematical thinking processes in solving mathematical problem-solving problems given. This type of research is descriptive qualitative with research subjects consisting of 6 students of class X Social Sciences SMA Islam Plus Adzkia Medan selected by purposive sampling method. The data collection technique was carried out using research instruments in the form of a description test which amounted to 3 questions and interviews. The results showed that the thinking processes used by students in solving problems were different. There are several problem-solving strategies used by students as a form of their thinking process. In the first question, there are three strategies used by students, namely act it out (conducting experiments), logical thinking, and different points of view. In the second question, all students used the strategy of registering all the possible answers that were explained directly or using the strategy of making tables. For the third question, there are two thinking strategies, namely by using formulas and strategies to find patterns. However, it was also found that there were still students who had inappropriate thinking processes.